MRI Findings of the Extensor Mechanism According to Trochlear Dysplasia Grade - PEKER A. A.; YILMAZ T. F.; AKÇAY A.; Atay M.; TABAR M.; BELGE M. N.; DÖNMEZ Z.; ŞAHİN D.; UÇAN V.; TOPRAK H. (My University, 2026)
Purpose To evaluate MRI findings of the extensor mechanism - including tendinopathy, fat pad edema, and enthesophytes - in patients with varying grades of trochlear dysplasia (TD), and to investigate the relationship between TD severity, TT-TG distance, and patellofemoral maltracking. Materials and Methods This retrospective cross-sectional study included 138 knees from 127 patients with MRI-confirmed TD. TD was graded on axial images using the Dejour classification (types A-D) and grouped as low-grade (type A) or high-grade (types B-D). TT-TG distances and lateral trochlear inclination (LTI) angles were measured on axial MRI. Extensor mechanism findings, including quadriceps and patellar tendinopathy, fat pad edema, insertional bone marrow edema, and enthesophytes, were assessed and compared across TD grades. Statistical analyses included chi-square, Mann-Whitney U, and Spearman correlation tests. Associations between TD severity and MRI findings were further evaluated using generalized estimating equation (GEE) models adjusting for age and sex, with additional models including TT-TG distance and LTI angle to assess independence from maltracking parameters. Results Increasing TD severity was associated with a greater TT-TG distance and lower TI angle (both p <0.001). In multivariable analysis, increasing TD severity was independently associated with distal quadriceps tendinopathy (OR = 2.19 per grade increase, 95% CI: 1.41-3.41; p <0.001), and this association remained significant after adjustment for TT-TG distance and LTI angle (OR = 1.11 per grade increase, 95% CI: 1.02-1.21; p = 0.012). No independent association was observed between TD severity and other extensor mechanism findings. Superior pole enthesophytes were associated with age rather than TD severity. Conclusion In conclusion, higher-grade trochlear dysplasia is associated with a greater TT-TG distance, a lower LTI angle, and a higher likelihood of distal quadriceps tendinopathy. Trochlear dysplasia is associated with a greater TT-TG distance and lower LTI angle. In addition, increasing TD severity is independently associated with distal quadriceps tendinopathy. These findings suggest that trochlear morphology may contribute to extensor mechanism stress beyond geometric maltracking parameters and highlight the role of MRI in detecting secondary soft-tissue changes in patellofemoral malalignment.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Radyoloji Nükleer Tıp ve Medikal Görüntüleme; Klinik Tıp; Klinik Tıp (Med); Radiology Nuclear Medicine & Medical Imaging; Clinical Medicine; Clinical Medicine (Med); Radyoloji ve Ultrason Teknolojisi; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiological and Ultrasound Technology; Radiology, Nuclear Medicine and Imaging